Late recurrence of low-grade serous carcinoma of the ovary mimicking colorectal neoplasia - Torres Avelar de Lima, Mateus; Oliveira Rocha, Cauã; Onofre de Brito Lima, Jéssica; Spader Casagrande, Aline; Lorenzoni Almeida Ghezzi, Caroline (Clinical and Biomedical Research, 2021)
A case report (images in medicine) of late recurrence of low grade serous carcinoma of the ovary mimicking colorectal neoplasia.